Oxford textbook of public health - Detels, Roger; Beaglehole, Robert; Lansang, M. Ann; Gulliford, Martin (Oxford medical publications, 2011)
A fifth edition of the hugely successful, internationally recognised textbook on public health and epidemiology, comprehensively covering the scope, methods and practice of the discipline.